(1,10-phenanthroline-2 N,N′)zinc(II)-4,4′-bipyridine (2/1) - Tan, Kong Wai; Ng, S.W.; Maah, Mohd Jamil; Ng, C.H. (International Union of Crystallography, 2009)
The ZnII atom in the title compound, [Zn(C14H 11N3O2S)(C12H8N 2)]·0.5C10H8N2, is N,N′-chelated by the N-heterocycle and N,O,S-chelated by the deprotonated Schiff base in a square-pyramidal environment. The hydr-oxy group of the Schiff base is a hydrogen-bond donor to 4,4′-bipyridine, which is located about a center of inversion, resulting in the formation of a supra-molecular trimeric unit. © 2009 Tan et al.